2022
DOI: 10.3390/jof8010063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trichoderma asperellum 6S-2 on Apple Tree Growth and Replanted Soil Microbial Environment

Abstract: Trichoderma asperellum strain 6S-2 with biocontrol effects and potential growth-promoting properties was made into a fungal fertilizer for the prevention of apple replant disease (ARD). 6S-2 fertilizer not only promoted the growth of Malus hupehensis Rehd seedlings in greenhouse and pot experiments, but also increased the branch elongation growth of young apple trees. The soil microbial community structure changed significantly after the application of 6S-2 fertilizer: the relative abundance of Trichoderma inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The benefit of Trichoderma as plant growth regulator was also reported in wheat growing with T. reesei, with increased numbers of shoots, higher weight of dried and fresh shoots, higher root length and root numbers (Ikram et al, 2019). The Trichoderma asperellum strain 6S-2 promoted the growth of apple seedlings in greenhouse, and also enhanced branch elongation of young apple trees (Wang et al, 2022).…”
Section: Discussion Discussion Discussionmentioning
confidence: 78%
“…The benefit of Trichoderma as plant growth regulator was also reported in wheat growing with T. reesei, with increased numbers of shoots, higher weight of dried and fresh shoots, higher root length and root numbers (Ikram et al, 2019). The Trichoderma asperellum strain 6S-2 promoted the growth of apple seedlings in greenhouse, and also enhanced branch elongation of young apple trees (Wang et al, 2022).…”
Section: Discussion Discussion Discussionmentioning
confidence: 78%
“…Bacillus not only inhibited the reproduction of pathogenic fungi, improved microbial community structure, and enhanced plant disease resistance but also secreted catabolic phytase to increase the amount of free phosphorus in the soil, promoted phosphorus uptake by plants, and improved the crop yield . Making fungi fertilizer from Trichoderma asperellum strain both promoted replanted seeding growth and development, optimized the soil microhabitats, and effectively alleviated ARD . In aquatic and terrestrial habitats, Lophiostom commonly occurs as sapwood on branches, stems, or bark in woody and herbaceous plants .…”
Section: Discussionmentioning
confidence: 99%
“… 59 Making fungi fertilizer from Trichoderma asperellum strain both promoted replanted seeding growth and development, optimized the soil microhabitats, and effectively alleviated ARD. 60 In aquatic and terrestrial habitats, Lophiostom commonly occurs as sapwood on branches, stems, or bark in woody and herbaceous plants. 61 Intaraudom et al 62 found that the secondary metabolites of Lophiostoma bipolare BCC25910 had no obvious inhibitory effect on disease-causing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental evidences in our systems suggest that the soil available nutrients and the nitrogen-fixing ability of B. megaterium increased with the increase in concentration of root exudates. Some studies have also demonstrated that the root exudates of Ageratina adenophora , maizes, and apple trees significantly increase the abundance of Bacillus in the soil and the soil available nitrogen ( Sun et al., 2021 ; Wang et al., 2021 ; Wang et al., 2022 ). The interactions among plant-microbes-nutrient may give positive feedback on the exotic plants ( Arafat et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%